EFISIENSI DAN EFEKTIVITAS BELANJA LANGSUNG PADA BALAI BAHASA PROVINSI SUMATERA SELATAN - Mayasari, Riana; Febriantoko, Jovan; Africano, Fernando; Loressa, Mesa (Universitas Muhammadiyah Palembang, 2021)
Budget as a means of controlling sources of public funds. New guidelines emerge for public sector organizations to pay attention to value for money in carrying out their activities. The benchmarks in the budget of an organization, both private and public sector organizations include economic assessment, effectiveness and efficiency. Effectiveness Budget is one of the principles in the organization of an organization, to be able to determine the level of achievement of organizational goals. This study focuses on the efficiency and effectiveness of Direct Expenditure Finance at the Language Center of South Sumatra Province. The purpose of this study was to determine the level of efficiency and effectiveness of direct expenditure performance at the Language Center of South Sumatra Province 2014-2017. The results showed that the level of efficiency and effectiveness of direct spending fluctuates every year. Suggestions for future research are to become input, improve coordination between fields and increase socialization and technical guidance